2014
DOI: 10.1016/j.biocel.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Exercise alters liver mitochondria phospholipidomic profile and mitochondrial activity in non-alcoholic steatohepatitis

Abstract: Mitochondrial membrane lipid composition is a critical factor in non-alcoholic steatohepatitis (NASH). Exercise is the most prescribed therapeutic strategy against NASH and a potential modulator of lipid membrane. Thus, we aimed to analyze whether physical exercise exerted preventive (voluntary physical activity - VPA) and therapeutic (endurance training - ET) effect on NASH-induced mitochondrial membrane changes. Sprague-Dawley rats (n=36) were divided into standard-diet sedentary (SS, n=12), standard-diet VP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 62 publications
3
31
0
2
Order By: Relevance
“…Here, we observed this condition in both mice genotypes, and 8 weeks of CAE intervention was able to reverse the lipid storage on hepatocytes, as well as decrease liver weight and liver damage. In accordance with our findings, Gonçalves et al () showed that regular aerobic training was effective in restoring mitochondial functions and reduce lipid storage in the liver in a NAFLD mouse model.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we observed this condition in both mice genotypes, and 8 weeks of CAE intervention was able to reverse the lipid storage on hepatocytes, as well as decrease liver weight and liver damage. In accordance with our findings, Gonçalves et al () showed that regular aerobic training was effective in restoring mitochondial functions and reduce lipid storage in the liver in a NAFLD mouse model.…”
Section: Discussionsupporting
confidence: 93%
“…Also, the liver, skeletal muscle and heart of the animals that ran had higher mitochondrial density. These observations are consistent with prior studies that reported that running has broad effects on mitochondrial respiratory function in the liver (Ardies et al, 1987;Gonçalves et al, 2014), skeletal muscle (Holloszy, 1967;Zoll et al, 2002;Votion et al, 2012) and heart (Kavazis et al, 2009a;Padrão et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Exercise was reported to alter the liver mitochondria phospholipidomic profile and maintain mitochondrial function in NASH [30]. A meta-analysis showed that weight loss ≥5% was related to an improvement in hepatic steatosis and weight loss ≥7% improved the NAFLD activity score [31].…”
Section: Discussionmentioning
confidence: 99%